Isotherms studies of equilibrium sorption of Cu2+ unto hydrochloric acid modified shrimp shell waste. (2022) - Nurfatihayati,; Azis, Yelmida; Mutamima, Anisa; Herman, Syamsu; Alfarisi, Cory Dian; Ikrima, Hadi
Abstract: Shrimp shell waste contains protein and chitin, which can be converted into chitosan. Chitosan compound was obtained from deacetylation of chitin and can be used as an adsorbent for various heavy metals. In this study, the shrimp processing industry's solid waste containing heads, shells, and tails was mashed and used directly to adsorb Cu 2+ ions. The adsorption process was carried out in batch mode with an adsorbate initial concentration (C0 ) of 40 ppm. The effects of several process parameters observed were contact time (0 to 180 min), adsorbent dosage (2.5, 5, 7.5, 10 g), and adsorption temperature (30, 40, and 50 °C). The equilibrium time for Cu 2+ ion adsorption using shrimp shell waste powder was attained at 150 min, with a concentration at equilibrium (Ce ) of 24.25 ppm. The highest adsorption capacity of 97.81% was obtained at an adsorbent dosage of 10 g and an adsorption temperature of 50 °C. The adsorption isotherm was studied using the Langmuir, Freundlich, Harkins Jura, Temkin, and Dubinin–Radushkevich (DRK) equations. Of the five adsorption isotherms used, the Harkin Jura isotherm model gives the highest R 2 value of 0.9891. Adsorption in this study includes physical adsorption with the heat of adsorption (ΔH) of 7.90 kJ/mol and endothermic adsorption.